Partial hepatectomy for a patient with Rendu–Osler–Weber disease: a case report - Naoko Sekiguchi; Daisaku Yamada; Shogo Kobayashi; Kazuki Sasaki; Yoshifumi Iwagami; Yoshito Tomimaru; Takehiro Noda; Hidenori Takahashi; Yuichiro Doki; Hidetoshi Eguchi (Surgical Case Reports, 2023)
Abstract Background Rendu–Osler–Weber disease (Osler disease) is a genetic disease with an autosomal dominant inheritance pattern. It is characterized by widespread telangiectasia in multiple organs. Liver involvement of FNH is relatively common, but liver cancer is very rare, and there are few reports on hepatectomy or postoperative complications. We report a very rare case in which hepatectomy was performed for a patient with Osler disease. Case presentation The patient was a 39-year-old man with Osler disease who had been previously diagnosed with multiple FNH and who had been followed for 8 years. During follow-up, the diameter of an S6 lesion gradually increased from 30 to 50 mm; no other lesions increased in size. We decided to perform partial liver resection as total biopsy for the growing tumor, due to the possibility that the growing tumor lesion included malignant components. The pathological examination revealed no obvious malignancy, which was finally diagnosed FNH. The postoperative course was uneventful and he was discharged on the 14th day after surgery. In the second month after discharge, he was transferred to our hospital with sudden abdominal pain in the right hypochondrium with severe tenderness. CT showed extravasation of contrast medium from the hepatic dissection surface in S6, and the hematoma extended to the pelvic floor. Emergency IVR was performed and revealed leakage of the contrast medium from the A6 branch. We embolized the A6 with Lipiodol. After embolization, there were no major problems, and the patient was discharged on the 9th day after the treatment. Conclusions Postoperative hemorrhage often occurs within 24 h after surgery, and 2 months after surgery is considered to be the late stage of the wound healing process, and postoperative hemorrhage at this timepoint is considered rare. This unexpected delayed postoperative hemorrhage may have been related to the etiology and pathology of Osler disease, nevertheless, case reports of hepatectomy for patients with Osler disease are limited. We, therefore, report the present case with a review of the relevant literature.